Pre- & post- retirement tips for librarians - Smallwood, Carol 1939- (American Library Association, 2012)
"Retirement raises many questions, and each librarian?s situation is unique. Our skills give us an edge in planning as well as managing our lives after library employment. This collection of essays should be an indispensable part of your retirement toolkit."--publishers description.